Anayasal Açıdan Orman - Kalmuk, Nisa (My University, 2024)
Ormanlar, 1982 Anayasası’nın “Ormanların Korunması ve Geliştirilmesi” başlığını taşıyan 169. maddesinde detaylı bir düzenlemeye konu edilmiştir. Çalışmamız kapsamında ormanların korunması ve orman alanlarının genişletilmesi için bir dizi güvence ve yasak öngören bu normun anlamını açıklığa kavuşturmayı amaçlıyoruz. Tez, giriş ve sonuç bölümleri dışında dört bölüme ayrılmıştır. “Nedenleri” başlığını taşıyan ilk bölümde normun anayasal varlık nedenleri ele alınmakta, hükmün öncelikle Anayasa’ya niçin girdiği sonrasında varlığının bugünkü ve gelecekteki olası nedenleri irdelenmektedir. “Lafzı ve Yeri” başlıklı ikinci bölümde normun dili, Anayasa sistematiği içindeki yeri ve gerçekleştirilmesini etkili kıldığını düşündüğümüz diğer bazı anayasal hak ve özgürlüklerle olan ilişkisi incelenmiştir. “Güvenceleri” başlığını taşıyan üçüncü ve “Yasakları” başlıklı dördüncü bölüm ise normun anlamının/ içeriğinin çözümlenmesine özgülenmiştir.

Forests are subject to a detailed regulation in Article 169 of the 1982 Constitution, titled “Protection and Development of Forests”. Within the scope of our study, we aim to clarify the meaning of this article, which provides for a series of guarantees and prohibitions for the protection of forests and the expansion of forest areas. The thesis is divided into four parts, except for the introduction and conclusion sections. The first section, titled “Reasons”, discusses the constitutional reasons for the existence of the article. Under this heading, firstly, why the article was included in the Constitution, and then the possible reasons for its existence today and in the future are examined. In the second chapter titled “Grammatical and Systematic Review”, the language of the article, its place in the Constitutional systematics and its relationship with some other constitutional rights and freedoms that we think make its realization effective are examined. The third section, titled “Assurances” and the fourth section, titled “Prohibitions”, are dedicated to analyzing the meaning/ content of the article.
Forest from a constitutional perspective
Keywords: anayasal boyutta orman; çevresel haklar forest; environmental rights; forest development; forest pretection; Forestry law and legislation; Kamu hukuku; orman; Ormancılık hukuku ve mevzuatı; ormanların geliştirilmesi; ormanların korunması; Public law; Turkey; Türkiye